The Influence of Online Public Opinion on Judicial Proceedings: A Comparative Legal Analysis of the Jiang Ge Case and Yao Jiaxin Case - Ma, Penghui (International Journal of Social Sciences and Public Administration, 2025)
As cyberspace increasingly becomes a "second space" in daily life, the impact of online public opinion on criminal judicial processes has grown significantly. However, online public opinion is often susceptible to manipulation or sensationalism by irresponsible media, ultimately jeopardizing judicial fairness and independence. Under the current framework of advancing the rule of law in China, it is imperative to address how to mitigate the negative effects of online public opinion on criminal justice while harnessing its positive role in promoting fairness. This paper takes the Jiang Ge case and Yao Jiaxin case as focal points, comparing criminal judicial practices in China and Japan from a comparative legal perspective to analyze conflicts between online public opinion and judicial rulings in China.